Gene divergence of homeologous regions associated with a major seed protein content QTL in soybean - Lestari, Puji; Van, Kyujung; Lee, Jay Ern; Kang, Yang Jae; Lee, Suk-Ha (Frontiers in Plant Science, 2013)
Understanding several modes of duplication contributing on the present genome structure is getting an attention because it could be related to numerous agronomically important traits. Since soybean serves as a rich protein source for animal feeds and human consumption, breeding efforts in soybean have been directed toward enhancing seed protein content. The publicly available soybean sequences and its genomically featured elements facilitate comprehending of quantitative trait loci (QTL) for seed protein content in concordance with homeologous regions in soybean genome. Although parts of chromosome (Chr) 20 and Chr 10 showed synteny, QTLs for seed protein content present only on Chr 20. Using comparative analysis of gene contents in recently duplicated genomic regions harboring QTL for protein/oil content on Chrs 20 and 10, a total of 27 genes are present in duplicated regions of both chromosomes. Notably, 4 tandem duplicates of the putative homeobox protein 22 (HB22) are present only on Chr 20 and this Medicago truncatula homolog expressed in endosperm at seed filling stage. These tandem duplicates could contribute on the protein/oil QTL of Chr 20. Our study suggests that non-shared gene contents within the duplicated genomic regions might lead to absence/presence of QTL related to protein/oil content.